Fundamental solutions of the Cauchy problem for some degenerate parabolic equations of the Kolmogorov type - Ivasyshen, S. D.; Layuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Fundamental solutions of the Cauchy problem for three classes of degenerate parabolic equations are investigated.These equations are natural generalizations of the classical Kolmogorov equation of the diffusion withthe inertia.